The Effect of Recruitment and Training on Commitment and Performance of Village Business Entity (Bumdes) Management in Kampar Regency Riau Province - Novianti Zalukhu; Susi Hendriani; Kurniawaty Fitri (Indonesian Journal of Economics, Social, and Humanities, 2020)
This study aims to determine the effect of recruitment and training on the commitment and performance of Village Bussiness Entity managers in Kampar district. The population in this study were all managers who were members of Village Bussiness Entity in Kampar Regency. Primary data in this study were collected by using questionnaire as research instrument to prove the results of the study. Multiple regression analysis with the assistance of the SPSS program was used to test the hypothesis in this study. The sampling technique was purposive sampling method (30 Village Bussiness Entity in 30 Kampar District Villages). The results showed that: 1) There's is positive and significant influence between recruitment and commitment of Village Bussiness Entity, 2) There was positive but not significant effect between training and commitment of Village Bussiness Entity managers, 3) There is positive and simultaneously significant effect between recruitment and training towards Village Bussiness Entity, 4) There is positive and significant effect between the commitment and performance of Village Bussiness Entity.